Discovery of benzamides as potent human β3 adrenergic receptor agonists. Issue 1 (1st January 2016) - Zhu, Cheng; Kar, Nam F.; Li, Bing; Costa, Melissa; Dingley, Karen H.; Di Salvo, Jerry; Ha, Sookhee N.; Hurley, Amanda L.; Li, Xiaofang; Miller, Randy R.; Salituro, Gino M.; Struthers, Mary; et al.
Graphical abstract: Abstract: The paper will describe the synthesis and SAR studies that led to the discovery of benzamide (reverse amide) as potent and selective human β3 -adrenergic receptor agonist. Based on conformationally restricted pyrrolidine scaffold we discovered earlier, pyrrolidine benzoic acid intermediate22 was synthesized. From library synthesis and further optimization efforts, several structurally diverse reverse amides such as24c and24i were found to have excellent human β3 -adrenergic potency and good selectivity over the β1 and β2 receptors. In addition to human β1, β2, β3 and hERG data, PK of selected compounds will be described.